Family- managed firms : founder presence and firm performance - Koh, Wei Jun (Nanyang Technological University, 2010)
This study examines the impact that the presence of a family firm's founder and proportion of family members on the board of directors have on the market value of publicly listed firms in Singapore. Based on a sample of 492 firms listed on the Singapore Stock Exchange (SGX), our results show no significant evidence to conclude a one-dimensional relationship between either founder presence or the proportion of family members on the board and firm performance. Rather, the interaction of both factors is found to have a significant effect on firm performance. Specifically, the proportion of family members on the corporate board is negatively associated with firm performance when the founder only holds the appointment of Board Chair.